Redescription of the endemic Australian cladoceran Alona willisi (Smirnov, 1989) and its assignment to Acanthalona gen. nov. (Cladocera: Anomopoda: Chydoridae) - Sinev, Artem Y.; Kobayashi, Tsuyoshi (Zootaxa, 2012)
Alona willisi (Smirnov, 1989) (Anomopoda: Chydoridae) is a poorly known cladoceran endemic to Australia. The presentmorphological study revealed numerous unique and rare features of the species and justifies its assignment to Acanthalona gen.nov. The new genus differs by its postabdomen armed with very long, thick marginal denticles and by exopodite of limb Vwith only three setae. It also differs from most Aloninae by antennal formula (setae 0-0-3/0-1-2, spines 1-0-1/0-0-1), sharedonly with Bryospilus Frey, 1980. In our opinion, Acanthalona gen. nov. is related to Armatalona Sinev, 2004 and MatralonaVan Damme & Dumont, 2009. These three genera form a clade, basal for the subfamily, and not directly related to the majorityof Aloninae. The records of A. willisi show that the species inhabits both acidic and alkaline freshwaters and seems to be algivorous as well as detritivorous.